Implementation of The Disaster Management Policy in The Sigi District (Study on Regional Disaster Management in The Sigi Regency) - Syahruddin Syahruddin; Rachmat Agung; Aenal Fuad Adam; Andri Irawan; Fransin Kontu (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
The objective of this research is to find out the implementation of disaster management policies in Sigi Regency which are focused on the rehabilitation and reconstruction phase of the earthquake and liquefaction post-disaster in Sigi Regency, namely the program of providing assistance to repair houses and permanent housing development assistance which is indeed the responsibility of the Regional Disaster Management Agency of Sigi Regency. It was a qualitative research method. Data were collected through observation, interview, and documentation. Researcher conducted interviews to 10 (ten) informants consisted of elements of program implementers and program recipients with questions related to 4 (four) aspects of the model of policy implementation from Thomas B. Smith. The results of the research show that the ideal policy aspect are implemented well while the aspect of Target Group, Implementing Organizations and Environmental Factors are not implemented well. Therefore, it can be concluded that the implementation of the disaster management policy of the rehabilitation and reconstruction phase of the program of providing assistance to repair houses for the community has not been implemented well.